Unipolar (Dendritic) Brush Cells Are Morphologically Complex and Require Tbr2 for Differentiation and Migration - McDonough, Ashley; Elsen, Gina E.; Daza, Ray M.; Bachleda, Amelia R.; Pizzo, Donald; DelleTorri, Olivia M.; Hevner, Robert F. (Frontiers in Neuroscience, 2021)
Previous studies demonstrated specific expression of transcription factor Tbr2 in unipolar brush cells (UBCs) of the cerebellum during development and adulthood. To further study UBCs and the role of Tbr2 in their development we examined UBC morphology in transgenic mouse lines (reporter and lineage tracer) and also examined the effects of Tbr2 deficiency in Tbr2 (MGI: Eomes) conditional knock-out (cKO) mice. In Tbr2 reporter and lineage tracer cerebellum, UBCs exhibited more complex morphologies than previously reported including multiple dendrites, bifurcating dendrites, and up to four dendritic brushes. We propose that "dendritic brush cells" (DBCs) may be a more apt nomenclature. In Tbr2 cKO cerebellum, mature UBCs were completely absent. Migration of UBC precursors from rhombic lip to cerebellar cortex and other nuclei was also impaired in Tbr2 cKO mice. Overall, cerebellar foliation was slightly reduced in Tbr2 cKO brain, likely reflecting defects of granule neuron development, a lineage in which Tbr2 is transiently expressed in granule neuron precursors. Our results indicate that UBC migration and differentiation are sensitive to Tbr2 deficiency. To investigate whether UBCs develop similarly in humans as in rodents, we studied Tbr2 expression in mid-gestational human cerebellum. Remarkably, Tbr2+ UBC precursors migrate along the same pathways in humans as in rodent cerebellum and disperse to create the same "fountain-like" appearance characteristic of UBCs exiting the rhombic lip.